AB0517 Tocilizumab monotherapy in the clinical practice: Retrospective analysis of a cohort of patients with active rheumatoid arthritis in catalonia, spain. (23rd January 2014) - Magallares, B.; Quesada, E.; Lisbona, M.P.; Calvet, J.; Sanmarti, R.; Reina, D.; Narvaez, J.; Diaz-Torne, C.; Marsal, S.; Maymo, J.; Garcia-Manrique, M.; Moreno, M.; et al.
Abstract : Background: New data indicates that Tocilizumab (TCZ) plus Methotrexate (MTX) does not have superior clinical efficacy to TCZ alone. Objectives: To evaluate demographic and clinical features of a cohort of patients with rheumatoid arthritis (RA) treated with TCZ monotherapy in the clinical practice Methods: Demographic and clinical data of 81 patients treated with TCZ monotherapy were assessed in 7 Spanish centers. Duration of RA, previous treatments, reason for DMARDs discontinuation and adverse events were included. Clinical activity assessed by Disease Activity Score (DAS) 28-ESR index, and laboratory data were done at weeks 0, 12 and 24 (W0, W12 and W24). Statistical analysis was performed using T-Student and Wilcoxon Tests Results: A total of 81 patients were evaluated. Mean age: 57.7±12.7 years and 81.2% females. At baseline, patients had mean disease duration of 13.2±9.4 years. 69.1% and 58.0% were Rheumatoid Factor and anti-CCP positive. Patients had been treated previously with Methotrexate (82.1%), Leflunomide (50.0%), hydroxycloroquine (21.8%), Gold Salts (16.7%), Cyclosporine (11.5%) and Salazopyrine (7.5%). Reasons for DMARD discontinuation previous TCZ monotherapy were: adverse effects 59.2%, inefficacy 26.3% and patient decision 7.9%. Patients had been treated with 3 (16.0%), 2 (21.0%) and 1 (30.9%) biological therapies before starting TCZ. TCZ was the first biological therapy in 12.3% of patients. Biological treatments previous TCZ were Etanercept (64.7%), Adalimumab (52.9%), Infliximab (47.1%), Rituximab (32.4%), Abatacept (25.0%) and Anakinra (5.9%). The mean (±SD) CRP, ESR, DAS28, SJC and TJC at W0 were 10.2±17.3 mg/dl, 41.9±31.4, 5.7±1.4, 7.7±6.9 and 11.0±7.6 respectively. At W12 and W24, 29.0% (n=18/62), 42.1% (n=24/57) of patients achieved DAS28 remission criteria and 46.8% (n=29/62), 59.6% (n=34/57) low disease activity respectively. We find a relationship between disease duration and the probability to achieve the remission at W12: T-test for equality of means: 15.2 (group no-remission) vs 10.1 years (group of remission), p=0.046. We also find relationship between the number of previous biological therapies and the probability to achieve the low disease activity at W12. T-test: 2.6 (group no-low disease activity) vs 1.7 (group of low disease activity), p=0.023. This relationship disappeared at W24 in both cases Conclusions: Our series of RA patients show the efficacy of Tocilizumab treatment administered as monotherapy in clinical practice. The main reason for using Tocilizumab monotherapy has been intolerance to DMARDs Disclosure of Interest: B. Magallares: None Declared, E. Quesada: None Declared, M. P. Lisbona: None Declared, J. Calvet: None Declared, R. Sanmarti Consultant for: Roche, D. Reina: None Declared, J. Narvaez: None Declared, C. Diaz-Torne: None Declared, S. Marsal: None Declared, J. Maymo: None Declared, M. Garcia-Manrique: None Declared, M. Moreno: None Declared, V. Hernández: None Declared, H. Corominas Consultant for: Roche, J. M. Nolla Consultant for: Roche